Juridical Review of the Position of Land Deed Drafting Officials (PPAT) in Implementing Deeds of Imposition of Mortgage Rights - Prasetyo, Bagus Agung Yuda; Fajar Riyanto, Taufan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to determine and analyze the position of Land Deed Making Officials (PPAT) in implementing Deeds of Encumbrance of Mortgage Rights, as well as to find out various obstacles and ways to overcome obstacles in the implementation of Imposition of Mortgage Rights. This research uses a sociological juridical approach. Data sources were obtained from several stages, namely through field research (interviews) and library research. Data analysis in a systematic way includes data reduction, data presentation and drawing conclusions. Based on research, it is concluded that the position of the Land Deed Making Officer (PPAT) in implementing the Imposition of Mortgage Rights is to bridge the interests of the debtor with the interests of the creditor so that both parties get a sense of justice. , usefulness, and legal certainty in binding mortgage guarantees. The obstacle experienced by PPAT in implementing the imposition of mortgage rights is that there are still banks that allow them to impose mortgage rights on land that has not been certified. However, this method can cause many risks. Keywords: Land; Registrar; Imposition; Mortgage; Position; Rights.